2020
DOI: 10.3389/feart.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of Standardized Precipitation Index Due to the Effects of Probability Distributions and Parameter Errors

Abstract: The standardized precipitation index (SPI) is widely used in drought assessments due to its simple data requirement and multiscale characteristics. However, there are some uncertainties in the process of its calculation. This study, taking the Heihe River basin in northwest of China as the study area, mainly focuses on the uncertainty issues both in SPI calculation and in drought characteristics associated with the probability distributions and parameter estimation errors. Ten probability distributions (two-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Here we use the parametric approach by fitting a Gamma ( E  ) distribution to the monthly precipitation at each grid. Although alternative distributions could have been used the Gamma distribution is the most widely used for SPI calculations (Zhang & Li, 2020). The Gamma cumulative distribution function is given by…”
Section: Methodsmentioning
confidence: 99%
“…Here we use the parametric approach by fitting a Gamma ( E  ) distribution to the monthly precipitation at each grid. Although alternative distributions could have been used the Gamma distribution is the most widely used for SPI calculations (Zhang & Li, 2020). The Gamma cumulative distribution function is given by…”
Section: Methodsmentioning
confidence: 99%
“…(1993), it is commonly thought that the two‐parameter gamma best fits any precipitation time series aggregated at any time scale. However, the later studies showed that this is not always the case in many areas of the world (Guttman, 1999; Angelidis et al ., 2012; Sienz et al ., 2012; Blain and Meschiatti, 2015; Stagge et al ., 2015; Svensson et al ., 2017; Zhang and Li, 2020), particularly in dry and semi‐dry climates (Guttman, 1999; Stagge et al ., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the performances of a dozen PDFs listed in Table 2 are evaluated over different climatic areas of Iran. These distributions are widely used in hydrological analysis and have already been examined for SPI calculation in different areas of the world (Guttman, 1999; Lloyd‐Hughes and Saunders, 2002; Ntale and Gan, 2003; Vicente‐Serrano, 2006; Wu et al ., 2007; Quiring, 2009; Angelidis et al ., 2012; Vicente‐Serrano et al ., 2012; Guenang and Kamga, 2014; Blain and Meschiatti, 2015; Stagge et al ., 2015; Zhang and Li, 2020). Table 2 introduces the selected distributions, the number of their parameters, and the methods used for their parameter estimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harisuseno [5] demonstrated that the SPI showed good reliability in assessing drought characteristics when compared with the RAI, while [6] utilized TRMM satellite data and SPI for monitoring and developing the spatiotemporal map of meteorological drought. Zhang and Li [7] examined the implications of different probability functions and parameter estimation on the SPI index, including drought intensity, duration, and frequency. The Standardized Precipitation Index (SPI) is more frequently applied to drought analysis regarding owing effortless calculation since the method is recommended by the World Meteorological Organization [8,9].…”
Section: Introductionmentioning
confidence: 99%